The evolution of transposable elements in humans and Drosophila - Styles, Pamela (2010)
The different genomic environments in which transposable elements reside in the Great Apes and the Drosophila result in substantial differences between the evolution of transposable elements in these two groups of organisms. In the Great Apes, where deletion of transposable elements is relatively rare, elements tend to be retained in the genome to the extent that complete sets of elements belonging to a particular transposable element family can be obtained. In Drosophila, there is a rapid turnover of transposable elements, imposing strong selection pressure on transposable elements to be able to infect new hosts. This study investigates the evolution of transposable elements in these two genomic environments.